A Study on the Application of Ecological linguistics to English Teaching - Kong, Lingdan (Pacific International Journal, 2024)
This paper explores the application of ecological linguistics to English teaching, highlighting its significance in enhancing language learning and promoting a deeper understanding of the interconnectedness between language, culture, and the environment. Ecological linguistics recognizes that language is inseparable from its social, cultural, and ecological contexts, emphasizing the role of context in language teaching. By incorporating ecological perspectives, English language educators can help learners comprehend how language usage varies across different contexts and how ecological factors influence linguistic choices, thereby improving learners’ ability to communicate effectively in real-world situations. Additionally, ecological linguistics promotes the use of authentic language materials and real-world contexts, exposing learners to diverse linguistic practices and cultural diversity. It also acknowledges language variation and diversity, fostering tolerance, inclusivity, and intercultural competence. Furthermore, the integration of language and culture is emphasized, promoting cultural awareness and sensitivity among learners. The paper proposes strategies for English teaching within the Ecological Linguistics Dynamic Mode, such as establishing clear and adaptive teaching objectives, utilizing diverse teaching approaches, and implementing dynamic assessment. By adopting these strategies, educators can create a comprehensive and meaningful learning experience that extends beyond language structures, equipping learners with the necessary linguistic and cultural tools to navigate a diverse and rapidly changing world.